KESULITAN MENGAJAR SISTEM REPRODUKSI MANUSIA PADA KELAS IX A SMP NEGERI 1 BALLA KABUPATEN MAMASA - Rambulangi, Elisaberth (Universitas Muhammadiyah Surabaya, 2025)
The purpose of this study was to determine the difficulty of teachers in the learning process of the subject of the human reproductive system in class IX A SMP Negeri 1 Balla, and to know the opinion of people (parents) about the teaching of the human reproductive system. This type of research is qualitative research. The population in this study, is all students of Class IX A Balla SMP Negeri 1 Balla school year 2014/2015 as many as 30 people. Samples using saturated sample, ie the entire population sampled, therefore this research, including the study population. Data collection, done by noting the difficulties encountered in the classroom, and a questionnaire to find out the opinion of the parents. Data analysis techniques, qualitative descriptive, which describe the difficulties encountered in the classroom, and the results of the questionnaire, described by calculating the percentage of respondents' opinions then narrated. The results showed that the difficulty of teaching the subject of the human reproductive system, consisting of two factors, namely internal factors that occur in the classroom through the interaction of teachers and students, and external factors are derived from the customs of the people that talk about the means of human reproduction was taboo and violating customs and habits in society.